OP0319 DIAGNOSTIC ACCURACY OF ULTRASOUND IN CALCIUM PYROPHOSPHATE DEPOSITION DISEASE: PRELIMINARY RESULTS OF THE OMERACT US IN CPPD SUB-GROUP. (June 2019) - Filippou, Georgios; Scanu, Anna; Adinolfi, Antonella; Toscano, Carmela; Largo-Carazo, Raquel; Naredo, Esperanza; Calvo, Emilio; Herrero-Beaumont, Gabriel; Zufferey, Pascal; Madelaine-Bonjour, Christel; Maccarter, Daryl; Makman, Stanley; et al.
Abstract : Background: 9The OMERACT Ultrasound (US) in calcium pyrophosphate deposition disease (CPPD) sub-task force has been working on the assessment of the utility of US in CPPD since 2014 first creating definitions for CPPD identification and then demonstrating that US is a reliable tool[1]. Objectives: Objective of this study is to assess the diagnostic accuracy of US in CPPD Methods: This is a multicentre international diagnostic accuracy study involving 17 centres from 9 countries. We enrolled in this study consecutive patients waiting to undergo knee replacement surgery due to severe osteoarthritis. Each patient underwent US examination of the knee, focusing on the menisci and the hyaline cartilage, the day prior to surgery, scoring each site according to the presence/absence of CPP as defined by OMERACT[1]. After surgery, the menisci and the condyles were collected and examined microscopically. Six samples were collected, both from the surface and from the internal part of menisci and cartilage trying to cover a large part of the structure. All slides were observed under transmitted light microscopy and by compensated polarised microscopy. A dichotomous score was given for the presence/absence of CPP crystals. US and microscopic analysis were performed by blinded operators. Sensitivity and specificity of US were calculated using microscopic findings of the menisci and cartilage as the gold standard. Results: These preliminary analyses include 30 patients. The mean age was 71yrs (SD±9.1), 19 (63%) were females. 17 patients were positive at US analysis and 12 at microscopic analysis. Diagnostic accuracy results of US at patient level, are presented in figure 1. Conclusion: These preliminary results demonstrate that US is a sensitive exam for identification of CPPD with acceptable specificity. US is the first diagnostic technique with consistent reliability and validity to be applied for non-invasive screening for CPPD in clinical practice. References: [1] Filippou G, Scirè CA, Adinolfi A, et al. Identification of calcium pyrophosphate deposition disease (CPPD) by ultrasound: reliability of the OMERACT definitions in an extended set of joints—an international multiobserver study by the OMERACT Calcium Pyrophosphate Deposition Disease Ultrasound Subtask Force. Ann Rheum Dis 2018;:annrheumdis-2017-212542. doi:10.1136/annrheumdis-2017-212542 Disclosure of Interests: Georgios Filippou Speakers bureau: Laborest, Abbvie, BMS, Sanofi, Anna Scanu: None declared, Antonella Adinolfi: None declared, Carmela Toscano: None declared, Raquel Largo-Carazo: None declared, Esperanza Naredo Consultant for: Abbvie, Speakers bureau: AbbVie, Roche, Bristol-Myers Squibb, Pfizer, UCB, Lilly, Novartis, Janssen, and Celgene GmbH, Emilio Calvo: None declared, Gabriel Herrero-Beaumont: None declared, Pascal Zufferey: None declared, Christel Madelaine-Bonjour: None declared, Daryl MacCarter: None declared, Stanley Makman: None declared, Zachary Weber: None declared, Ingrid Möller: None declared, Marwin Gutierrez: None declared, Carlos Pineda: None declared, Denise Clavijo Cornejo: None declared, Héctor García: None declared, Victor Ilizaliturri: None declared, Jaime Mendoza Torres: None declared, Raul Pichardo: None declared, Luis Carlos Rodriguez Delgado: None declared, Emilio Filippucci: None declared, Edoardo Cipolletta: None declared, Teodora Serban: None declared, Florentin Ananu Vreju Consultant for: abbvie and novartis, Speakers bureau: abbvie, novartis, pfizer, sandoz, eli lilly, ucb pharma, Gael Mouterde: None declared, Maria-Antonietta d'Agostino: None declared, Marcello Govoni: None declared, Leonardo Punzi Consultant for: BMS, Fidia, Grunenthal, Menarini, Speakers bureau: BMS, Fidia, Grunenthal, Menarini, Nemanja Damjanov Grant/research support from: AbbVie, Pfizer and Roche, Consultant for: Abbvie, Gedeon Richter, Merck, Novartis, Pfizer and Roche., Speakers bureau: Abbvie, Gedeon Richter, Merck, Novartis, Pfizer and Roche., Lene Terslev Speakers bureau: Speakers fee from : Roche, Novartis, Pfizer, MSD, BMS, Celgene, Irene Azzolin: None declared, Giulio Guerrini: None declared, Carlo Alberto Scirè: None declared, Annamaria Iagnocco: None declared